1983
DOI: 10.2105/ajph.73.5.521
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Cognitive Loss among Employed Men and Women

Abstract: -A representative sample of 1,367 employed men and women in Detroit responded to questions about their drinking practices and then completed a cognitive test which measures abstraction abili-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 14 publications
0
23
1
1
Order By: Relevance
“…Second, moderate alcohol use may actually improve cognitive functioning and so increase the efficiency of human capital production. Although studies examining the effect of drinking on cognition have found conflicting results ranging from large negative effects, to no effect, to positive effects of moderate drinking on cognition (Parker and Nobel 1977;Parker et al 1983;Hannon et al 1985;Carey and Maisto 1987;Elias et al 1999), there is at least some evidence that moderate drinking may improve cognitive functioning. Although the empirical model presented in this article is very different from those used by the previous alcohol-wage literature (e.g., Mullahy and Sindelar 1989;French and Zarkin 1995;Heien 1996), it is still useful to compare the results presented here with those of the previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, moderate alcohol use may actually improve cognitive functioning and so increase the efficiency of human capital production. Although studies examining the effect of drinking on cognition have found conflicting results ranging from large negative effects, to no effect, to positive effects of moderate drinking on cognition (Parker and Nobel 1977;Parker et al 1983;Hannon et al 1985;Carey and Maisto 1987;Elias et al 1999), there is at least some evidence that moderate drinking may improve cognitive functioning. Although the empirical model presented in this article is very different from those used by the previous alcohol-wage literature (e.g., Mullahy and Sindelar 1989;French and Zarkin 1995;Heien 1996), it is still useful to compare the results presented here with those of the previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…Because substantial evidence suggests a potential for a differential effect of alcohol use versus alcohol abuse on human capital accumulation and on health (Parker and Nobel 1977;Parker et al 1983;Hannon et al 1985;Carey and Maisto 1987;Dufour and Fe Caces 1993;Doll 1998;Elias et al 1999), equation (6) distinguishes simple or moderate alcohol use from heavy use. Term b w9 is the differential return to education associated with drinking (relative to no consumption), and b w10 is the additional increment to the returns to education associated with heavy drinking (relative to any consumption).…”
Section: B Empirical Modelmentioning
confidence: 99%
“…The higher depression symptom scores for women are consistent with previous studies.' 8 Quantity of alcohol consumed per usual drinking occasion is correlated with symptoms of depression while sober in both men (r = .19) and women (r = .13). Quantity consumed per occasion is the same alcohol variable which we previously reported to be associated with reduced cognitive functioning in this population.8 Frequency of alcohol use is less strongly correlated with depression symptoms in men (r = .06) and women (r = .06).…”
Section: Methodsmentioning
confidence: 98%
“…Research ®ndings have also been inconsistent in demonstrating eects of light to moderate drinking upon cognitive functioning. However, recent studies have suggested that drinking in excess of 30 standard drinks per week is associated with poorer performance on neuropsychological testing (Christian, 1995;Parker, 1983;Waugh, 1989). These studies of light to moderate drinking again do not examine the relationship of alcohol use to the development of dementia per se and for the most part have been studies of healthy middle aged adults.…”
Section: Neuropsychology and Neuropathologymentioning
confidence: 99%